2021
DOI: 10.3389/fmicb.2021.766464
|View full text |Cite
|
Sign up to set email alerts
|

Definition of CRISPR Cas12a Trans-Cleavage Units to Facilitate CRISPR Diagnostics

Abstract: The CRISPR diagnostic (CRISPR-Dx) technology that employs the trans-cleavage activities has shown great potential in diagnostic sensitivity, specificity, convenience, and portability, and has been recognized as the next-generation diagnostic methods. However, due to the lack of standardized definition of Cas trans-cleavage enzymatic units, it is difficult to standardize the present CRISPR-Dx systems, which have undoubtedly impeded the development of the CRISPR-Dx industry. To solve the problem, we here first s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 22 publications
2
52
1
Order By: Relevance
“…In addition to changing the divalent cations in the reaction buffer, the addition of additives can also improve the sensitivity of Cas12 system. Polyethylene glycol (PEG), glycerin and Triton X-100 can improve the sensitivity of Cas12a system, but their mechanism of promoting trans-cleavage activity is unknown [ 16 ]. Li et al [ 17 ] found that bovine serum albumin (BSA) could improve sensitivity of Cas12a system, while L-proline could protect Cas12a from an adverse environment.…”
Section: Strategies For Improving Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to changing the divalent cations in the reaction buffer, the addition of additives can also improve the sensitivity of Cas12 system. Polyethylene glycol (PEG), glycerin and Triton X-100 can improve the sensitivity of Cas12a system, but their mechanism of promoting trans-cleavage activity is unknown [ 16 ]. Li et al [ 17 ] found that bovine serum albumin (BSA) could improve sensitivity of Cas12a system, while L-proline could protect Cas12a from an adverse environment.…”
Section: Strategies For Improving Sensitivitymentioning
confidence: 99%
“…Yue et al [ 15 ] found that LbCas12a had the highest trans-cleavage activity under weakly alkaline conditions (pH 9). Lv et al [ 16 ] analyzed the trans-cleavage activity of LbCas12a in reaction buffers with pH ranging from 3.5 to 9.6 in increments of 0.1. Among the tested buffers, LbCas12a preferred buffers with pH 8.5 and 8.6.…”
Section: Strategies For Improving Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Yu and colleagues created an all-in-one TA test using the telomere-synthesis-induced CRISPR-Cas12a system [ 71 ]. Extension of the telomere by telomerase resulted in telomere repeats (TTAGGG)n, which could be recognized using a customized CRISPR-guided RNA (crRNA) and activated by the conventional trans-cleavage CRISPR- Cas12a detection assay [ 72 ]. Because CRISPR-Cas12a is so sensitive, this method achieved a linear regression spanning 100 to 2000 HeLa cells and a detection limit of only 26 HeLa cells [ 71 ].…”
Section: Targeting Telomerase By Crispr/casmentioning
confidence: 99%
“…The clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR associated proteins (Cas) systems have been considered to have great potential in diagnostic, thus revolutionizing the nucleic acid detection area (Wang et al, 2020b;Lv et al, 2021). The most commonly used Cas proteins in the CRISPR/Cas-based nucleic acid detection system are Cas9, Cas12, Cas13 and Cas14 (Wang et al, 2020e).…”
Section: Introductionmentioning
confidence: 99%